2017
DOI: 10.1038/s41598-017-08369-0
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation triggers endogenous activity patterns in cultured cortical networks

Abstract: Cultures of dissociated cortical neurons represent a powerful trade-off between more realistic experimental models and abstract modeling approaches, allowing to investigate mechanisms of synchronized activity generation. These networks spontaneously alternate periods of high activity (i.e. network bursts) with periods of quiescence in a dynamic state which recalls the fluctuation of in vivo UP and DOWN states. Network bursts can also be elicited by external stimulation and their spatial propagation patterns tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 81 publications
4
25
0
Order By: Relevance
“…Notably, in our cellular model of excitotoxicity, pretreatment with BDNF for 1 h could not prevent the decrease in neuronal viability () or interfere the processing of TrkB‐FL () induced by NMDA. Basal TrkB activation, observed in this experiment (, lower panels) as before (Du et al , ; Gomes et al , ; Vidaurre et al , ), might be due to spontaneous neuronal activity of dissociated cultures (Pasquale et al , ) and mediated by calcium‐influx through NMDARs and calcium channels (Du et al , ). Next, we were interested in establishing the phosphorylation status of the TrkB‐FL receptor preserved in excitotoxic conditions by TFL 457 action.…”
Section: Resultssupporting
confidence: 76%
“…Notably, in our cellular model of excitotoxicity, pretreatment with BDNF for 1 h could not prevent the decrease in neuronal viability () or interfere the processing of TrkB‐FL () induced by NMDA. Basal TrkB activation, observed in this experiment (, lower panels) as before (Du et al , ; Gomes et al , ; Vidaurre et al , ), might be due to spontaneous neuronal activity of dissociated cultures (Pasquale et al , ) and mediated by calcium‐influx through NMDARs and calcium channels (Du et al , ). Next, we were interested in establishing the phosphorylation status of the TrkB‐FL receptor preserved in excitotoxic conditions by TFL 457 action.…”
Section: Resultssupporting
confidence: 76%
“…Similarity between spontaneous and evoked activity patterns was previously described in a number of in vivo studies [33] [34] and a recent study has confirmed such observation in vitro [35]. In this work, similarly to what previously described [12,27,29,30] we employed polymeric structures made of polydimtheylsiloxane (PDMS) for confining neurons (Mata et al, 2005;Liu et al, 2005;del Campo & Greiner, 2007Jackman et al, 1999 to induce the self-organization of networks into inter-connected spatially defined neuronal assemblies.…”
Section: Introductionsupporting
confidence: 74%
“…Another important ingredient of the network connectivity in our model is the presence of a small percentage of neurons that has higher incoming connection strengths, and is responsible for focusing the noise and initiating the collective activity (and avalanche propagation). The presence of a few highly active sites, driving cortical neural activity (leaders), has been reported experimentally [29,[70][71][72]. Notably it has been shown that these leader sites are reliably and rapidly recruited within both spon-taneous and evoked bursts [71].…”
Section: Discussionmentioning
confidence: 99%